Removal of the herbicide Glyphosate using activated carbon impregnated with metallic compounds of silver and copper to improve water quality - Rubio, Andressa Jenifer; Bergamasco, Rosângela; Yamaguchi, Natália Ueda (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
With the increasing use of several pesticides in agriculture, including the Glyphosate which is the herbicide most widely consumed worldwide, there is a need for the development of diversified and effective water treatment, since glyphosate consumption can cause serious health problems on animals, humans and plants. As an alternative treatment, the removal of glyphosate from the water can be obtained with the use of activated carbon, and further to leverage its results, may be used the impregnation of silver and copper on the activated carbon, since the activated carbon in the purest form it is marketed often not sufficiently effective for removing some pollutants. Therefore, this study aimed at the removal of glyphosate by an adsorption process using activated carbon impregnated with 0.5% silver and 0.5% copper with the aim of increasing the adsorption efficiency when compared to activated carbon. It was observed that the removal of glyphosate is improved when using the impregnated metal compounds, being 66.1% with the adsorbent GAC / AgCu and only 21.1% with GAC. It is still needed profound research related to characterization and adsorption experiments to better explain the adsorption mechanism that occurs in this process. However, it can be concluded that the granular activated carbon soaked with 0.5% silver and copper developed in the present work may be named as a possible technology for improving the quality of water intended for human consumption for removal of the glyphosate herbicide.